Increasing complexity in small-angle X-ray and neutron scattering experiments: from biological membrane mimics to live cells. Issue 2 (27th February 2020) - Semeraro, Enrico F.; Marx, Lisa; Frewein, Moritz P. K.; Pabst, Georg
Abstract : We review compositional models for analyzing small-angle X-ray and neutron scattering data of complex membrane mimics and live cells. Abstract : Small-angle X-ray and neutron scattering are well-established, non-invasive experimental techniques to interrogate global structural properties of biological membrane mimicking systems under physiologically relevant conditions. Recent developments, both in bottom-up sample preparation techniques for increasingly complex model systems, and in data analysis techniques have opened the path toward addressing long standing issues of biological membrane remodelling processes. These efforts also include emerging quantitative scattering studies on live cells, thus enabling a bridging of molecular to cellular length scales. Here, we review recent progress in devising compositional models for joint small-angle X-ray and neutron scattering studies on diverse membrane mimics – with a specific focus on membrane structural coupling to amphiphatic peptides and integral proteins – and live Escherichia coli . In particular, we outline the present state-of-the-art in small-angle scattering methods applied to complex membrane systems, highlighting how increasing system complexity must be followed by an advance in compositional modelling and data-analysis tools.